(untitled) - A. R. L. (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Nevodovsky, G. S., 1956: Flora sporovych rostenij Kasachstana. T. 1. Rzavcennyje grily (Flora de las royas del Kasachstan, T. 1. Uredinaceae) 1-431, 1 retrato, 257 fig. Alma Ata. (1962)

(untitled)
Fil: A. R. L..